Hubungan Lingkungan dan Disiplin Kerja terhadap Kinerja Guru dalam Proses Pembelajaran - Dina Sri Nindiati; Ermini Ermini (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the relationship between the work environment and work discipline, both partially and on the performance of teachers at SMK PGRI 1 Palembang. The type of research used in this research is descriptive analysis with a quantitative approach to describe the relationship between variables through hypothesis testing. This study used a questionnaire as a data collection tool which was distributed to 42 respondents from SMK PGRI 1 Palembang. Based on the results of the research conducted, there is a simultaneous significant relationship between the Work Environment and Work Discipline variables on the Teacher Performance variable in the Learning Process. This is evidenced by obtaining Fcount 6.622 which is greater than Ftable 2.850. In addition, it is known that partially the Work Environment (X1) has no relationship with Teacher Performance (Y). This is evidenced by the acquisition of tcount 1.078 < ttable 2.023, and coefficient 0.288. Meanwhile, Work Discipline (X2) has a positive and significant relationship to Teacher Performance (Y). This is evidenced by the acquisition of tcount which is greater than ttable (2.782 > 2.023) and the coefficient is 0.008 and the value is positive. Keywords: work environment, work discipline and teacher performance